Zarządzanie modernizacją w kontekście współczesnych teorii zarządzania strategicznego - Wojtołowski, N.W.; Chomiakow, S.F. (Modernization management in the context of contemporary strategic management theory, 2006)
The paper indicates modernization as the key aspect in the development of contemporary businesses. Resource based theory of strategic management is shown as limited in effective implementation of modernization, especially in the case of restricted competitive pressure. Completion of this approach with elements of positioning approach seems desirable as it determines the ultimate concept of modernized company’s functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 310-314